Epidemiology of Clostridium difficile infection Among Patients with Newly Diagnosed or Relapsed Acute Leukemia: A Single-center Experience. (4th October 2017) - Garcia, Alexandra Franco; McMillen, Tracy; Chow, Hoi Yan; Eagan, Janet; Sun, Janine; Kamboj, Mini
Abstract: Background: Patients undergoing treatment for hematologic malignancy are at a higher risk for developing Clostridium difficile infection (CDI). We sought to determine the epidemiology of toxigenic C. difficile (TCD) carriage and CDI incidence among patients undergoing with newly diagnosed or relapsed acute leukemia. Methods: Serial stool samples were collected from 92 patients with new or relapsed acute leukemia admitted at Memorial Sloan Kettering Cancer Center between August 26, 2011 to January 22, 2013. Only the first hospitalization during this time period was included. Screening was performed by toxigenic culture and polymerase chain reaction for tcdB gene regardless of symptoms of diarrhea. Genotyping was done by Multi Locus Sequence Typing (MLST). Acquisition of TCD, development of CDI, and associated clinical variables were recorded. Results: A total of 92 patients were enrolled in the study. The mean age was 54.3 (median 57.5, range 21–86), 51 were male (55%). The majority (86, 93%) had newly diagnosed acute leukemia and 7% had relapsed disease. 60 patients (65%) had recent healthcare-related exposure, among these were 35 (38%) patients newly referred another facility. The most common chemotherapy regimen was Daunorubicin + Cytarabine in 71 subjects (77%). Systemic antibiotics of any duration during the same hospitalization were used in 89 patients (97%). Median length of stay (LOS) was 30.5 days (range 6–140 days). Among the 92 subjects, 17 developed CDI within 90 days (18%), 12 (71%) had CDI during the index admission. Five among these 12 had known TCD colonization, genotyping of colonizing and CDI strains from the same patients were identical for all patients. CDI in subsequent hospitalizations occurred in 5 patients, 4/5 were new acquisitions. One patient with TCD colonization never developed CDI. 53 subjects (58%) underwent stem cell transplant at a median time of 4 months (range 2–19 months), 8 (15%) developed CDI within 30 days of the transplant admission. Conclusion: CDI is exceedingly common among patients with acute leukemia. Acquisition of TCD and CDI occurs early in the treatment course. Approximately half of infections occur in patients with known TCD colonization. Extended LOS and high antibiotic usage are contributors to the high burden of CDI among this population. Disclosures: All authors: No reported disclosures.